2013
DOI: 10.2147/ijn.s42736
|View full text |Cite
|
Sign up to set email alerts
|

The prospective protective effect of selenium nanoparticles against chromium-induced oxidative and cellular damage in rat thyroid

Abstract: Background: Nanotechnology has enabled researchers to synthesize nanosize particles that possess increased surface areas. Compared to conventional microparticles, it has resulted in increased interactions with biological targets. Objective: The objective of this study was to determine the protective ability of selenium nanoparticles against hexavalent chromium-induced thyrotoxicity. Design: Twenty male rats were used in the study, and arbitrarily assigned to four groups. Group 1 was the control group, and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Accumulating evidence supports the idea that Se nanoparticles have antioxidant effects59. These effects have been shown to increase the activities of both GPX and glutathione S-transferase and induce less oxidative stress3459. The same consequences were observed in this study, in which the porous Se@SiO 2 nanocomposite simulation significantly decreased the ROS levels and improved the cells’ tolerance to H 2 O 2 (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Accumulating evidence supports the idea that Se nanoparticles have antioxidant effects59. These effects have been shown to increase the activities of both GPX and glutathione S-transferase and induce less oxidative stress3459. The same consequences were observed in this study, in which the porous Se@SiO 2 nanocomposite simulation significantly decreased the ROS levels and improved the cells’ tolerance to H 2 O 2 (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, the porous Se@SiO 2 nanocomposites may not only reduce the expression of the ROS directly but also provide essential elements that help to comprise the intracellular pool against oxidative stress5758. Accumulating evidence supports the idea that Se nanoparticles have antioxidant effects59. These effects have been shown to increase the activities of both GPX and glutathione S-transferase and induce less oxidative stress3459.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be attributed to apoptosis and thyroid toxicity explained by Escribano et al [11]. Congested blood vessels observed in this study were in accordance with that reported by Yu et al [41] and Hassanin et al [17]. They explained that oxidative stress and lipid peroxidation might affect vascular walls, leading to their dilatation and congestion.…”
Section: Discussionsupporting
confidence: 91%
“…They have been found to be active against human breast cancer cells [48]. There is a clear correlation between the nanoparticles size and their biological activity [49]. Thus, these reports clearly justify the efficient synthesis and stabilisation of SeNPs from the ethanol extract of propolis.…”
Section: Discussionmentioning
confidence: 89%